KONSTRUKSI IDENTITAS POSTMODERN DALAM IKLAN LA LIGHT VERSI âDONT QUITâ - Surahman, Sigit (KEMADHA, 2012)
n the postmodern era and the economic, political , social and cultural erraticÂ inÂ IndonesiaÂ todayÂ , presentÂ the medium ofÂ televisionÂ ledÂ to a new phenomenonÂ inÂ theÂ worldÂ ofÂ audioÂ visualÂ advertisingÂ .Â Cigarette advertising LA LIGHT version of